Contested terrain: explaining divergent patterns of public opinion towards immigration within Europe - Heath, Anthony (2019)
Mass immigration has become an enduring feature of open, integrated and dynamic economies, with most wealthy post-industrial societies experiencing large migration inflows in recent years (OECD 2017). At the same time, public opposition to immigration has become a major disruptive force in developed democracies, with the emergence of a new family of political parties, the populist radical right (Mudde 2007), who draw their support primarily from voters who oppose immigration (Ivarsflaten 2008). Immigration is economically vital yet politically contentious. Indeed, the present political and academic relevance of this topic area is greater than ever due to the Great Recession of 2008 which resulted in increased anti-immigrant sentiments in several countries (Billiet, Meuleman, and De Witte 2014; Kuntz, Davidov, and Semyonov 2017), large flows of refugees into both old and new immigration countries in Europe, and widespread political repercussions, with views of immigration for example playing a significant role in the British vote to leave the EU. However, citizens vary widely in their views of migration overall (Meuleman, Davidov, and Billiet 2009; Ford and Lymperopoulou 2017), and not all migrant-receiving countries exhibit public hostility to migration to the same degree (Heath and Richards, 2019). Understanding what drives these individual and cross-national variations in public support for or opposition to immigration is therefore an issue of central importance for academics and policymakers alike.The goal of this special issue is to report findings from papers aiming to explain the drivers of attitudes toward immigration in European countries and how patterns vary across Europe. The articles in the special issue address questions such as: Do some members of European publics oppose immigration because they believe it threatens their economic interests, or because they see it as a threat to the national culture and values? How accurate are people’s perceptions of the number of immigrants in their country, and do misperceptions lead to greater hostility towards immigration? To what extent are individuals’ perceptions of threat shaped by more fundamental influences such as basic human values, racist beliefs, group identities and the associated feelings of relative deprivation? How far do these shape feelings of threat or misperceptions of the volume of immigration?